Status of and Threats to Waterbirds of Rupa Lake, Pokhara, Nepal - Kafle, Gandhiv; Cotton, Marcus; Chaudhary, Jhalak R; Pariyar, Hari; Adhikari, Hari; Bohora, Som B; Chaudhary, Umesh K; Ram, Ashok; Regmi, Bimal (Journal of Wetlands Ecology, 2008)
Rupa Lake is the third biggest lake of Pokhara valley. It supports a number of floral and faunal species. A total of 36 species of waterbirds have been recorded in the lake which represents about 19 percent of the total 193 wetland-dependent birds found in Nepal. The lake is under pressure from diverse anthropogenic factors. Waterbirds of Rupa Lake face a number of threats including trapping/hunting, fish farming using nets, habitat destruction by soil erosion, sedimentation and agricultural conversion, human disturbance, water pollution and eutrophication. This article provides an overview of waterbirds and threats to them in Rupa Lake Area. Key words: Rupa Lake, waterbirds, threats DOI: 10.3126/jowe.v1i1.1569 Journal of Wetlands Ecology Vol.1(1/2) 2008, p.9-12